Heterogeneity and the Distance Puzzle - Elizaveta Archanskaia; Guillaume Daudin (FIW - Research Centre International Economics, 2012)
This paper shows that reduced heterogeneity of exporter-specific goods can provide a direct explanation of the distance puzzle. Using COMTRADE 4-digit bilateral trade data we find that the elasticity of trade to distance has increased by 8% from 1962 to 2009. Theoretical foundations of the gravity equation indicate that the distance coefficient is the product of the elasticity of trade costs to distance and a measure of heterogeneity, e.g. the substitution elasticity between exporter-specific goods in the Armington framework. This parameter has increased by at least 12-29% from 1962 to 2009. The evolution of the distance coefficient is thus compatible with a 4-16% reduction in the elasticity of trade costs to distance.
Keywords: F15; N70; 330; gravity equation; distance puzzle; trade elasticity; trade costs